Neutrophil NETs in reproduction: from infertility to preeclampsia and the possibility of fetal loss - Hahn, Sinuhe; Giaglis, Stavros; Hoesli, Irene; Hasler, Paul (Frontiers in Immunology, 2012)
The intention of this review is to provide an overview of the potential role of neutrophil extracellular traps (NETs) in mammalian reproduction. Neutrophil NETs appear to be involved in various stages of the reproductive cycle, starting with fertility and possibly ending with fetal loss. The first suggestion that NETs may play a role in pregnancy-related disorders was in preeclampsia, where vast numbers were detected in the intervillous space of affected placentae. The induction of NETosis involved an auto-inflammatory component, mediated by the increased release of placental micro-debris in preeclampsia. This report was the first indicating that NETs may be associated with a human pathology not involving infection. Subsequently, NETs have since then been implicated in bovine or equine infertility, in that semen may become entrapped in the female reproductive during their passage to the oocyte. In this instance interesting species-specific differences are apparent, in that equine sperm evade entrapment via expression of a DNAse-like molecule, whereas highly motile bovine sperm, once free from seminal plasma that promotes interaction with neutrophils, appear impervious to NETs entrapment. Although still in the realm of speculation it is plausible that NETs may be involved in recurrent fetal loss mediated by anti-phospholipid antibodies, or perhaps even in fetal abortion triggered by infections with microorganisms such as L. monocytogenes or B. abortus.